Assessment of heterobeltiosis and useful hererosis for seed yield and its components in (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Ninety six crosses of Indian mustard [Brassica juncea (L.) Czern & Coss.] obtained by crossing of forty eight lines with two testers in a line x tester fashion were used to assess the possibility of estimating the amount of heterosis for seed yield, yield components and oil content. These parents and crosses were grown in randomized complete block design replicated thrice and observations were taken on days to maturity, plant height at maturity (cm), number of branches plant-1, number of siliquae plant-1, seed yield plant-1 (g), and oil content (%). Heterosis of higher magnitude was expressed for seed yield plant-1 and number of siliqua plant- 1. The crosses ACN-9 x ACN-169 and Pusa bold x ACN-164 were identified as the superior crosses which can be utilized for development of high yielding genotypes.